A Review of Treatment Methods Using Electrical Stimulation - Jaber, Nasma Adnan; Noori, Aiyah Sabah; Hussien, Emad Eyad; Jaber, Maha Adnan (Journal of medical and pharmaceutical sciences, 2022)
This article deals with a theoretical study of methods of electrical stimulation therapy which is one of the physical therapy used to treat pain and increase the strength of the weak muscle where the treatment is done by connecting electrodes to the patient which in turn deliver electrical impulses through nerve paths at specific intervals. Also, the relationship between methods of electrical stimulation and types of electric current has been shown in this review, Stimulation methods were divided according to the type of current used where continuous current is used in the case of galvanic with high frequency and low current. Methods (Trabert, Leduc, Faradic, H-wave, Micro-current) use the pulse current with a frequency not exceeding 1000 Hz, while methods like Transcutaneous Electrical Nerve Stimulation (TENS), Four-pole interfering, Two-pole interfering, Isoplaner interfering, Neuromuscular, dipole interfering, diadynamic use alternating current with a frequency between (3600 Hz - 10000 Hz) and the value of the current is between (50 mA - 140 mA). The most important effect or use of electrical stimulation is to reduce pain (Analgesic effect), as well as, 2-pole and 4-pole interference effect on myorelaxation and spasmolytic. Finally, there are many studies that show that there are no long-term side effects of electrical stimulation, only some temporary effects resulting from the misuse of electrodes for the stimulation device or resulting from the use of high currents.